Relationship on Knowledge Level of Nurses About Prevention of Decubitus Towards Stroke Patients in The Inpatient Room - Herlina, Meriani (Universitas Aisyah Pringsewu, 2020)
The decubitus is damage to the integrity of the skin or can be said to be a wound due to trauma and surgery as well as a chronic disease caused by prolonged pressure on the skin which causes irritation. This study aims to determine the relationship between the level of knowledge of nurses in preventing pressure sores on stroke patients in the inpatient room. By conducting a study entitled the relationship between the level of knowledge of nurses about prevention of pressure sores on stroke patients in the inpatient room at RSU Imelda Workers Indonesia Medan in 2020. This research is a quantitative study using a descriptive correlation design with a cross-sectional approach. The population in this study were nurses who served in the inpatient room as many as 133 nurses and the sample in this study was 57 nurses based on sampling technique. While the incidence at Imelda Hospital Medan based on the level of knowledge of nurses based on the majority of respondents whose age interval is 20-25 years as many as 25 people (44%), while the minority of respondents whose age interval is 41-45 years are 5 people (9%). Based on the majority of respondents whose last education interval was D3 as many as 35 people (61%), while the minority of respondents whose last education interval was Nurses were 4 people (7%). Based on the majority of respondents whose gender interval is female as many as 34 people (60%), while the minority of respondents whose gender interval is male as many as 23 people (40%). And the majority of respondents whose working period interval is less than 1 year are 19 people (33%), while the minority of respondents whose working period is 7-8 years are 23 people (40%). ), while as many as 16 people (28%), and less than 10 people (18%). Conclusions were obtained based on the research. The level of knowledge of nurses about decubitus in the Imelda Hospital inpatient room, Medan, was that most nurses already understood. And the suggestion from the researcher is that it is highly expected to be able to further improve the right service for stroke patients in the Imelda Hospital inpatient room, Medan.